Using authentic doctor–patient consultations in improving communication skills - Yeh, Meng; Hsu, Wei‐li (Foreign language annals, 2023)
The Challenge There is an increasing interest in using authentic doctor–patient consultations as teaching materials for courses of languages for medical purposes. However, what is the effect of the instruction? How does the instruction adopt authentic consultations advance students' interpersonal communicative competence in medical settings? This paper aims to answer these questions. This study investigates the effect of an instructional design for medical Chinese, which incorporates research findings from Conversation Analysis (CA) and uses authentic doctor–patient consultations in primary‐care visits as teaching materials. The goal of the instruction is to develop students' interpersonal communicative competence in medical settings, especially doctor–patient consultations. Twelve pre‐med college students in the course Chinese for Healthcare Professions participated in this study. They first participated in five 50‐min classes using a chapter from a medical Chinese textbook. Then, they participated in an additional set of five 50‐min instructional sessions introducing CA‐informed instruction using authentic consultations. The pedagogical effects were measured with paired roleplays administered at three different times: at the beginning of the course, after the regular instruction sessions, and, finally, after the CA‐informed instructional period. The results show that the CA‐informed instruction for using authentic doctor–patient consultations has a positive effect on improving students' communicative performance in simulated medical settings.